Endoscopic Endonasal Odontoidectomy: Nuances of Neurosurgical Technique - Romero, Flavio Ramalho [UNESP]; Vieira, Rodolfo Brum [UNESP]; Ancheschi, Bruno da Costa [UNESP] (Georg Thieme Verlag Kg, 2018)
Odontoidectomy is the treatment of choice for some diseases that cause irreducible ventral compression of the brainstem. In this study, we present our series emphasizing the technical nuances of endoscopic endonasal odontoidectomy.
Keywords: craniocervical junction; odontoidectomy; endoscopic endonasal approach; transoral approach